Learning to teach through video playback: student teachers confronting their own practice. Issue 1 (2nd January 2019) - Sagasta, Pilar; Pedrosa, Begoña
ABSTRACT: The aim of this study was to examine the use of video playback with student teachers to promote teacher learning and to analyse patterns of reflection. A total of 14 student teachers video recorded their lessons in the practice setting and later confronted their performance, facing their videotaped lesson during the course of an interview with their university supervisor. The interviews were then transcribed and coded. Our results indicate that video playback facilitates student teacher learning and that the quality of reflection ranges from routine to dialogic. This suggests that further research into how to elicit higher levels of reflection is needed. The role of the supervisor in promoting deeper thinking should be further examined.